2019
DOI: 10.5812/jjhs.84966
|View full text |Cite
|
Sign up to set email alerts
|

Control of Silt Density Index of Osmosis Membranes Through Chlorine Injection and its Effect on Cartridge Filter Replacement Period

Abstract: Background: Various suspended organic and inorganic contaminants including biological deposits, different types of algae and barnacles and causative factors of water turbidity result in irreparable damages to pretreatment systems and membranes in reverse osmosis systems. Objectives: In this study, the effect of injection of disinfectant materials such as calcium hypochlorite on the reduction of silt density index (SDI) value at the inlet of reverse osmosis system has been investigated. Methods: In this researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In addition, by analyzing the reasons, it is possible to find a suitable method for chemical cleaning of the membranes (11). Many studies have been done in details regarding the fouling reasons through which one or two reasons have been identified, however, there are less global or comprehensive studies in this regard (12)(13)(14)(15)(16)(17)(18)(19). In a study by Gutiérrez Ruiz et al, which is similar to the recent study, chemical composition and structure of fouling agents on the membrane surface were determined using the energy dispersive X-ray microanalysis and scanning electronic microscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, by analyzing the reasons, it is possible to find a suitable method for chemical cleaning of the membranes (11). Many studies have been done in details regarding the fouling reasons through which one or two reasons have been identified, however, there are less global or comprehensive studies in this regard (12)(13)(14)(15)(16)(17)(18)(19). In a study by Gutiérrez Ruiz et al, which is similar to the recent study, chemical composition and structure of fouling agents on the membrane surface were determined using the energy dispersive X-ray microanalysis and scanning electronic microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the presence of calcium carbonate and excess colloidal silica intensifies the deposition on the membrane and clogging and decreases the permeate flux (17). In another study by Fayaz et al, the effect of disinfectants injection was evaluated to find the reduction of SDI efficiency, and it was revealed that injection of chlorine in the inlet of RO system can increase the lifetime of cartridge filters, and significantly, reduce the operation costs (19). Given the importance of desalination plants to supply the water needed for communities and industries in southern Iran, it is important to pay attention to the technical and economic aspects of this category.…”
Section: Introductionmentioning
confidence: 99%